2008
DOI: 10.1007/s11547-008-0292-3
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of liver cirrhosis by transit-time analysis at contrast-enhanced ultrasonography

Abstract: Analysis of the time of onset of US contrast enhancement of the hepatic vein appears to be a potentially useful noninvasive supplement to conventional sonography and Doppler in the follow-up of patients with chronic diffuse liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 32 publications
(45 reference statements)
2
24
0
Order By: Relevance
“…In our study, the hepatic vein arrival time gradually decreased with the severity of fibrosis, as reported in the literature most based on the patients with chronic hepatitis C (Albrecht et al 1999;Hirota et al 2005;Lim et al 2006;Sugimoto et al 2002), but significant changes were found only when cirrhosis was present; the hepatic artery and portal vein arrival times were not significantly changed with the progress of liver fibrosis. In contrast, intrahepatic transit times (HA-HVTT and PV-HVTT) decreased with the progression of fibrosis, consistent with the literature (Pedersen et al 2005;Abbattista et al 2008;Staub et al 2009) and were significantly correlated with the stages of liver fibrosis. PV-HVTT even became a negative number in some cirrhotic patients.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the hepatic vein arrival time gradually decreased with the severity of fibrosis, as reported in the literature most based on the patients with chronic hepatitis C (Albrecht et al 1999;Hirota et al 2005;Lim et al 2006;Sugimoto et al 2002), but significant changes were found only when cirrhosis was present; the hepatic artery and portal vein arrival times were not significantly changed with the progress of liver fibrosis. In contrast, intrahepatic transit times (HA-HVTT and PV-HVTT) decreased with the progression of fibrosis, consistent with the literature (Pedersen et al 2005;Abbattista et al 2008;Staub et al 2009) and were significantly correlated with the stages of liver fibrosis. PV-HVTT even became a negative number in some cirrhotic patients.…”
Section: Discussionsupporting
confidence: 90%
“…The titles and abstracts of these studies were reviewed; 170 were excluded based on the selection criteria, and 12 were ultimately identified as relevant to our review. Therefore, we analyzed these 12 studies13,2636 and the 844 included patients, as shown in Table 1 and Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies used a Siemens Sequoia ultrasound system (Siemens Healthcare, Erlangen, Germany) 13,27,28,3133,35. GE Logiq system (General Electric Healthcare, Milwaukee, WI, USA) was used in two of the studies,26,34 while a Toshiba system (Toshiba Corporation, Tokyo, Japan) was used in two other studies 29,30. With regard to contrast, there were five studies13,27,28,32,33 that used Levovist, the first-generation contrast agent.…”
Section: Resultsmentioning
confidence: 99%
“…A possible explanation may be the uptake or trapping of Levovist MBs in the sinusoids of the liver, that occurs until larger arterovenous shunting, typical of cirrhosis, has occurred [127]. Using Sonovue, the cut-off value to identify cirrhosis appeared shorter and namely 17 seconds, a value that showed excellent sensitivity and specificity [128,129]. However, the case series was small and the data have not been replicated in further centres so far.…”
Section: Hepatic Vein Transit Time (Hvtt)mentioning
confidence: 96%